Predictive factors and renal outcomes in childhood systemic lupus erythematosus - Zawavi, Mohd Haikal Abdullah (2023)
This study aims to define predictive factors of kidney involvement in a cohort of paediatric patients with SLE. Studies have sought to identify early clinical features, laboratory tests, and molecular mechanisms that are associated with unfavorable renal prognosis, to optimize the surveillance and interventions in these patients. Method: A retrospective cross-sectional study was conducted at Hospital Universiti Sains Malaysia (USM), Kelantan, Malaysia. A total of 101 patients were diagnosed with Systemic Lupus Erythematosus. aged below 18 years old were recruited for this study. Demographic data (age, gender, race, height, weight, body mass index, parent’s monthly income, family history of Systemic Lupus Erythematosus and blood pressure), age during diagnosis of Lupus Nephritis, duration between onset of SLE and Lupus Nephritis, clinical factors (hypertension, anemia), Laboratory factors (proteinuria, hypoalbuminemia, hematuria eGFR, serum creatinine level, dsDNA positivity, and Histological WHO Class renal biopsy) were obtained from the patient’s medical records. Descriptive and simple linear regression was used to investigate predictors for renal outcomes, and prognostic analyses were performed. Multivariate logistic regression analysis was performed to determine independent predictors of renal outcomes. Result: One hundred and one children and adolescents with SLE were recruited in the cohort. Majority of them were females (93.1% with mean age 12.4 years old). 65 of them have lupus nephritis with biopsy proven of class IV and above in 53 (81.5%) of them. Presence of hypertension, abnormal eGFR, and histological biopsy of diffuse proliferative glomerulonephritis were initially identified as significant variables, however, only the latter two factors were found to be significantly predicting complication of CKD (OR 11.8, 95 %CI 2.22-63.5), (OR 29.9, 95% CI 3.05-294), respectively. The Kaplan Meier mortality survival analysis among patients with CKD also demonstrated 5- and 10-years mortality were 64% and 43%, respectively. Conclusion: Lupus Nephritis has been demonstrated to be associated with poor clinical outcomes and high mortality. Histological findings of diffuse proliferative disease and abnormal eGFR of stage IV onwards had been shown to be significantly associated with CKD. Lupus Nephritis children with CKD had mortality rate of almost 50% within 5 years.